Kinerja Keuangan Dan Potensi Kebangkrutan Dari Perusahaan Transportasi Pelayaran Pada Tahun 2013-2017 - Aditya Budi Kurniawan dan Carunia Mulya Firdausy (Universitas Tarumanagara, 2019)
The purpose of this study is to analyze the financial performance and potential bankruptcy of shipping transportation companies listed in the Indonesia Stock Exchange in 2013-2017. the method to estimate financial performance and bankruptcy prediction is by using financial ratio & Altman Z-Score method. The results show that the majority of companies indicating there is a signs of improving financial performance when commodity prices begin to recover. In addition to the analysis of the Altman Z-score bankruptcy Based on the Z-score value of the 14 sample companies, in 2013 there were 5 companies in the healthy category (z-score> 2.60), however in 2016 this number decreased to 3 companies . Whereas for companies that are in the grey area category (z-score 1.1-2.60) in 2013 there were 4 companies and then declined to the remaining 3 companies in 2016. Whereas in 2013 company is in the category of financial distress (z-score <1 , 1) there are 5 companies and increased to 8 companies in 2016. In 2017 there was an increase in the companies in the healthy category & grey area each into 4 companies. While companies in the financial distress category are reduced to 6 companies. This means there are improvements in 2017.